The Role of Future Self-Guides in Motivated Language Learning Behaviors: The Case of English and Chinese Language Learners in Thailand - Zhang, Xiaopeng; Laohawiriyanon, Chonlada (Journal of Liberal Arts Prince of Songkla University, 2023)
Based on the 2x2 model of future self-guides, a revision of future self-guides which is used to explain students’ motivated behaviors in language learning, this mixed-method study investigated: (1) the extent to which students’ motivations to learn English and Chinese are regulated by each component of future self-guides; (2) the relationship between future self-guides and motivated language learning behaviors; and (3) students’ perceived motivation in learning English and Chinese. Motivational questionnaires were distributed to 136 Thai university students (64 English majors and 72 Chinese majors), and follow-up semi-structured interviews were conducted with 15 English majors and 15 Chinese majors. The results showed that the students’ motivations to learn English and Chinese were highly regulated by future self-guides. It was also found that Ideal L2 Self from own standpoint was the component that was most highly correlated with motivated language learning behaviors for both English and Chinese majors, followed by Ideal L2 Self from other standpoint, and Ought-to L2 Self from own standpoint respectively. Ought-to L2 Self from other standpoint showed the weakest correlation to motivated language learning behaviors. The interview data indicated that the instrumental values of the target languages, significant others’ expectations, and perceived self-obligations were perceived as contributing factors to their motivation to learn both languages. This paper offers pedagogical implications as well as recommendations for further research.